Penggunaan Metode Diskusi untuk Meningkatkan Hasil Belajar Materi Perubahan Sosial pada Siswa Kelas XII SMA Negeri 4 Pekanbaru - Ermi, Netti (SOROT, 2015)
Abstract The purpose of this study is to know how the discussion method implemented and to know the increase of students’ achievement on social changing topic in sociology subject at SMA Negeri 4 Pekanbaru. Based on the result of examination, it was found that most students cannot reach the minimum achievment criterion (KKM). To solve this problem, the researcher used discussion method. The data of this study are taken from students score on pre-test and post -test. The result of pre-test showed that only 9 (25.71 %) students reach KKM while 26 (71.29%) students cannot reach KKM. After using discussion method in cycle 1, it was found at the first activity, there were 12 (31.29%) sgtudents reached KKN while 23 (65.71%) students cannot reach KKM and at the second activity there were 24 (68.7%) students reached while 11 students cannot reach KKM. The result of cycle 2 showed that at the first activity there were 27 (77.14%) students reaxhed KKM whille 8 (22.86%) cannot reach KKM and at the second activity there were 35 (100%) students reached KKM. It is concluded that the discussion method can increase twelve grade students’ achievment in social changing topic in sociology subject at SMA Negeri 4 Pekanbaru.